Ruslan Russian 1 a communicative course for beginners in Russian - Langran, John; Veshneva, Natalia (Ruslan Limited, 2021)
Ruslan Russian 1 is the book for beginners. There is an introduction to the cyrillic alphabet followed by 10 lessons. The lessons are based on a series of compelling dialogues set in Moscow, and with an exciting story line, telling the story of Lyudmila and her three admirers, and with the "typical foreigner" struggling to understand life in Russia today. The lessons are traditionally laid out, with cartoons to introduce the language topics, dialogues, vocabularies, grammar explanations, background information, and lots of exercises for listening, speaking, reading and writing. There is not too much grammar to put learners off, but enough to give beginners a solid basis for further study. There is a 750 word dictionary and a key to the exercises at the back of the book. This course is widely used in the UK by schools, universities, adult education colleges and private language schools, as well as for 1:1 tuition. It is also useful for self tuition when used together with the Ruslan 1 Workbook.